2022
DOI: 10.3390/s22218294
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Damage Diagnosis of Reinforced Concrete Columns and Joints Strengthened with FRP Ropes Using Piezoelectric Transducers

Abstract: Recent research has indicated that the implantation of a network of piezoelectric transducer patches in element regions of potential damage development, such as the beam–column joint (BCJ) area, substantially increases the efficacy and accuracy of the structural health monitoring (SHM) methods to identify damage level, providing a reliable diagnosis. The use of piezoelectric lead zirconate titanate (PZT) transducers for the examination of the efficiency of an innovative strengthening technique of reinforced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Eventually, the changes caused in the specimen through the progressive loading process led to modifications to the position and the shape of the acquired voltage responses compared to the pristine condition. Consequently, it could be assumed that the peak frequency response alterations measured at the end of each loading step depict the material’s damage state in the transducer’s contiguity [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, the changes caused in the specimen through the progressive loading process led to modifications to the position and the shape of the acquired voltage responses compared to the pristine condition. Consequently, it could be assumed that the peak frequency response alterations measured at the end of each loading step depict the material’s damage state in the transducer’s contiguity [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, strain gauges are locally limited, while PZT transducers can act in a wide spatial region. However, a combination of both methods could exhibit supplementary data for verifying the attained data [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recently developed technology of SHM for RC structures focuses on identifying premature debonding of FRP strengthening materials [ 41 ]. Several studies investigate the ability of PZT transducers to identify the interfacial damage between FRP laminates and concrete as flexural reinforcement in the bottom surface of the specimens [ 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the above literature review, although research has been conducted in the direction of FRP debonding damage detection utilizing SHM systems based on a variety of methods, there is no generally accepted, reliable system that can be utilized in practice. In previous investigations, the authors proposed a wireless SHM system, which demonstrated promising results in damage detection of reinforced concrete [ 27 , 28 ], fiber reinforced concrete [ 35 ], and reinforced concrete strengthened with FRP ropes [ 41 ]. The successful application of this system toward the detection of damage due to FRP sheet debonding could verify to the system’s ability to identify a wide range of different types of damages and possibly lay the groundwork for its use in real structures.…”
Section: Introductionmentioning
confidence: 99%
“…Structural health monitoring (SHM) has been employed in various fields as a cost-effective maintenance strategy based on sensing systems, such as acoustic emission [ 1 , 2 ], piezoelectric [ 3 , 4 ], vibration [ 5 , 6 ], and multi-source sensors [ 7 , 8 , 9 ]. SHM data are utilized in diagnostics and prognostics.…”
Section: Introductionmentioning
confidence: 99%